Pengaruh Current Ratio (CR), Net Profit Margin (NPM), dan Kebijakan Dividen terhadap Harga Saham pada Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Periode 2013-2017 - Hottua Samosir; Enda Noviyanti Simorangkir; Andhy Stephanus; Krisna Emalini M Ginting; Yeyen Syarival Banjarnahor; Meita Pitriyani Br Sitepu (Owner : Riset dan Jurnal Akuntansi, 2019)
This research is meant to find out the effects of current ratio (cr), net profit margin (npm) and dividend policy on stock price in consumer goods companies which are listed in Indonesia Stock Exchange (IDX)in 2013-2017 periods. Sample determination using purposive sampling method and sample studied are 19 companies. Method of data analysis using multiple linear regression. The results of this research shows that simultaneously and partial CR, NPM and Dividend Policy have positive and significant effects to the stock price in consumer goods companies which are listed in Indonesia Stock Exchange in 2013-2017 periods.